Overcoming the Character Crisis in Children: Strategies, Outcomes, and Evaluations of Bina Desa Program - Oktriani, Dilla Rifa; Hufad, Achmad; Utami, Nindita Fajria (Utamax : Journal of Ultimate Research and Trends in Education, 2023)
To address Indonesia's character crisis marked by bullying and negative behavior in students, Yayasan Pemuda Peduli Bandung has introduced the Bina desa Program, incorporating experiential learning. This program emphasizes crucial character traits such as creativity, curiosity, responsibility, activeness, self-confidence, empathy, and cooperation. Through the involvement of families, schools, and communities, the program aims to enhance character education and make a positive contribution to the nation's development. This research analyzes the program's strategies, outcomes, and evaluation methods to improve character development initiatives in Indonesia. The study employs a qualitative approach, utilizing interviews, observations, and documentation for data collection and analysis. 17 Participants, namely CEOs, program developers, volunteers, and community stakeholders, were selected through purposive sampling. The data underwent rigorous analysis, ensuring validity and reliability. The implications of this study highlight the importance of character development programs in combating the character crisis. By implementing a comprehensive curriculum and employing the principles of experiential learning, programs i.e., bina desa can effectively foster essential character traits in children. Continuous evaluation, feedback, and improvement are crucial elements for ensuring the program's success. Moreover, the involvement of social agents and collaboration with various stakeholders are vital for creating a supportive environment that nurtures children's character. This study underscores the significance of character education in broader societal progress and emphasizes the role of well-designed programs in shaping exceptional individuals who contribute positively to society.